First human facial retransplantation: 30-month follow-up. Issue 10264 (28th November 2020) - Lantieri, Laurent; Cholley, Bernard; Lemogne, Cedric; Guillemain, Romain; Ortonne, Nicolas; Grimbert, Philippe; Thervet, Eric; Lellouch, Alexandre G
Summary: Background: Since the first successful facial transplantation in 2005, the benefits of this procedure in terms of aesthetics, functionality, and quality of life have been firmly established. However, despite immunosuppressive treatment, long-term survival of the allograft might be compromised by chronic antibody-mediated rejection (CAMR), leading to irreversible necrosis of the tissue. In the absence of therapeutic options, this complication is inevitably life-threatening. Methods: We report facial retransplantation in a man, 8 years after his first facial transplantation because of extensive disfigurement from type 1 neurofibromatosis and 6 weeks after complete loss of his allograft due to severe CAMR. We describe the chronology of immune-related problems that culminated in allograft necrosis and the eventual loss of the facial transplant, the desensitisation protocol used for this highly immunosensitised recipient, the surgical technicalities of the procedure, the specific psychological management of this patient, and the results from follow-up at 30 months. Findings: Although the patient had a complicated postoperative course with numerous immunological, infectious, cardiorespiratory, and psychological events, he was discharged after a hospital stay of almost 1 year. He has since been able to re-integrate into his community with acceptable restoration of his quality of life. Interpretation: This clinical report of the first documented human facial retransplantation is proof-of-concept that the loss of a facial transplant after CAMR can be mitigated successfully by retransplantation combined with an aggressive desensitisation process. Funding: Hôpital Européen Georges Pompidou, Assistance Publique-Hôpitaux de Paris.